Budaya Bertoilet: Duduk atau Jongkok? - Martosenjoyo, Triyatni (ETNOSIA : Jurnal Etnografi Indonesia, 2016)
AbstractPublic toilet is one of the important parts of the building that many aspects of design have to be Â taken into account to build. Many public Â toilets are built just by looking at the outer performanceÂ without considering whether or not the target user will fit with the design. This article deals withÂ this. It examines how toilet is perceived by the users, what type of toilet is preferred and why, andÂ how they utilize public toilet. The interaction between western and eastern culture in the toiletdesign has resulted in cultural shock and stuttering technology among the toilet users in regard toÂ the use of toilet because the influx of western culture is not balance with the introduction of theÂ new culture. Whether one chooses squatting or sitting toilet, it is not only related to universalÂ issues about modernity, luxury, cleanliness, and health. Toilet is not solely function as a disposalÂ waste container, but it is also a place for one to seclude him/herself from others, to relax and toÂ create new ideas. Toilet is a symbol to show onesâ identity. But how one use the toilet is closelyÂ associated with oneâs perception about toilet, gender, health, cleanliness, Islamic ethics, and bodyÂ proportion. Key words: toilet, sitting toilet, squatting toilet, modernity.